Adsorção de fenol de soluções aquosas utilizando cinzas provenientes da queima de bagaço de cana como adsorvente - Corrêa, Jenifer Toledo (Universidade Federal de São Carlos, 2025)
Water contamination by phenolic compounds is a major environmental issue due to their high toxicity and low biodegradability. Adsorption is an efficient and low-cost technique for the removal of such pollutants, especially when using alternative materials derived from agro-industrial residues. Therefore, the aim of this work was to evaluate the adsorption performance of phenol using raw and sodium hydroxide- treated sugarcane bagasse ash, investigating structural modifications and their effects on adsorption efficiency. The samples were characterized through iodine number and methylene blue number tests, indicators of microporosity and mesoporosity, respectively, and subjected to adsorption kinetic experiments. The experimental data were fitted to pseudo-first-order and pseudo-second-order kinetic models.The results showed a significant increase in porosity after alkaline treatment, with iodine and methylene blue numbers nearly doubling. The treated ash exhibited greater efficiency and faster phenol removal, with the pseudo-second-order model providing the best fit, indicating that chemisorption is predominant.It is concluded that NaOH-treated sugarcane bagasse ash is a sustainable and low-cost alternative for treating phenol-contaminated wastewater.
Adsorption of phenol from aqueous solutions using ashes from burning of sugarcane bagasse as adsorbent
Keywords: Adsorção; Fenol; Adsorvente; Cinzas de bagaço de cana; Tratamento de efluentes; Adsorption; Phenol; Adsorbent; Sugarcane bagasse ash; Wastewater treatment; ENGENHARIAS::ENGENHARIA SANITARIA::TRATAMENTO DE AGUAS DE ABASTECIMENTO E RESIDUARIAS; 6. Água Potável e Saneamento; 11. Cidades e Comunidades Sustentáveis; 14. Vida na Água